2009
DOI: 10.1007/bf03327446
|View full text |Cite
|
Sign up to set email alerts
|

A novel model of integrated care for the elderly: COPA, Coordination of Professional Care for the Elderly

Abstract: Despite strong evidence for the efficacy of integrated systems, securing the participation of health professionals, particularly primary care physicians (PCPs), has proven difficult. Novel approaches are needed to resolve these problems. We developed a model - COPA - that is based on scientific evidence and an original design process in which health professionals, including PCPs, and managers participated actively. COPA targets very frail community-dwelling elders recruited through their PCP. It was designed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…This is consistent with the literature emphasizing the significance of integrated care for the elderly [33-35]. Still, when need factors were controlled for, municipalities with integrated health and social care sectors had similar patterns in access to care and similar costs as compared to municipalities without such integration.…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with the literature emphasizing the significance of integrated care for the elderly [33-35]. Still, when need factors were controlled for, municipalities with integrated health and social care sectors had similar patterns in access to care and similar costs as compared to municipalities without such integration.…”
Section: Discussionsupporting
confidence: 89%
“…In recent years, the French system has studied the potential of case management, often taking disease management as a starting point, as reflected in a report by the General Inspectorate of Social Affairs [20]. Some recent experiments in France at the local level [21] or at multiple sites [22] have tested the integration paradigm. The preliminary results have been promising, prompting decision makers to consider implementing this organizational model at a larger scale.…”
Section: Recent Reforms To Integrate Carementioning
confidence: 99%
“…Multidisciplinary approaches have been trialled and discussed in a range of health care settings, including maternity and child health services (Schmied, Mills et al 2010), chronic headache care (Gaul, Bromstrup et al 2011), community-dwelling elders (Vedel, De Stampa et al 2009), eczema sufferers (van Gils, van der Valk et al 2009) and has been found to optimise patient outcomes in palliative care for lung cancer (Borneman, Koczywas et al 2008) and short bowel syndrome (Modi, Langer et al 2008). The dynamics of multidisciplinary teams have been studied in post-cancer follow-up care (Leib, Cieza et al 2011) and maternity care (McIntyre, Francis et al 2011), as well as in a hospital setting (Hogan, Barry et al 2011).…”
Section: Innovations In the Treatment Of Multimorbidity And Implicatimentioning
confidence: 99%